Home in a Hybrid World : Or to Dwell in a Networked Environment. - Pot, Martin. (River Publishers, 2020)
This book explores what it means to have a home in such a networked world. It describes what architecture can, or perhaps should, contribute to enable a more participatory role for inhabitants.